Measuring Ratchet Effects within a Firm: Evidence from a Field Experiment Varying Contractual Commitment - Charles Bellemare; Bruce Shearer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We present results from a field experiment designed to measure the importance of managerial commitment to a contract within a firm that pays its workers piece rates. In the tree planting industry the piece rate paid to workers is determined as a function of the difficulty of the terrain to be planted. During the experiment, workers began planting a terrain at a trial piece rate, but were told this rate would be revised upwards if, after a few work days, average average productivity was below that observed on a similar (control) terrain on which the firm had committed to the contract. Our results suggest that worker productivity was 20% to 40% lower in the absence of commitment. The reduction was less pronounced when workers had less time to benefit from any subsequent increase in the piece rate. This provides support for models of worker turnover as a means of overcoming ratchet effects.
Keywords: J33; M52; C93; 330; Ratchet effect; piece rates; incentive contracts; field experiments